Teenagers' Motive in Cyberbullying Against Micro-Celebrities on Social Media - Afrania Annastri; Medo Maulianza; Anindita Lintangdesi Afriani; Nur Asni Gani (CHANNEL: Jurnal Komunikasi, 2021)
Cyberbullying is a form of social media abuse most often carried out by teenagers because there are no specific requirements to examine how to use social media. Uniquely, the impact of cyberbullying in Indonesia can make victims viral and famous categorized as Micro-Celebrities. Micro-Celebrities are the ones famous for their content broadcasted through social media. This research aims to explain teenagers' motives in doing cyberbullying against Micro-Celebrities through social media. The research method used is descriptive qualitative with a phenomenology approach. Data is collected through in-depth interviews with female teenage informants 15 – 17 years of age. The research was conducted at SMAN 4, Bekasi City, located in a suburban area where most teenagers are heavy social media users. Summary of research result shows that teenagers’ motives to do cyberbullying against Micro-Celebrities are: (1) feeling dislike of micro-celebrities personality; (2) intending to insinuate with unethical negative comments; (3) feeling envious and intending to incite; (4) feeling that micro-celebrities do not deserve popularity when compared to macro-celebrities. Cyberbullying by teenagers against micro-celebrities is in the form of negative comments in the comments column. These micro-celebrities are being bullied because they are considered to have gained popularity by spreading harmful content. Teenagers disagree with celebrities who are instantly famous because it is very unfair to celebrities who have creations and positively benefit society.